Performance evaluation and some durability characteristics of environmental friendly palm oil clinker based geopolymer concrete. (10th September 2017) - Kabir, S.M. Alamgir; Alengaram, U. Johnson; Jumaat, Mohd Zamin; Yusoff, Sumiani; Sharmin, Afia; Bashar, Iftekhair Ibnul
Abstract: Huge demand for concrete due to industrialization and urbanization has resulted in the depletion of natural resources and led to an ecological imbalance. Hence, this research focuses on alternative materials, including the utilization of waste materials as a replacement for binders and conventional aggregates. Palm oil fuel ash (POFA), ground granulated blast furnace slag (GGBS) and metakaolin (MK) were used as binders; while palm oil clinker (POC) and oil palm shell (OPS) used as coarse aggregate in producing geopolymer concrete. Seven concrete mixtures were designed with varying coarse aggregate contents to develop eco-friendly geopolymer concrete while other parameters were kept constant. The mechanical properties and some durability characteristics of lightweight geopolymer concrete were investigated and reported. The highest compressive strength achieved was 41.5 MPa at 28 days where 100% POC (9–14 mm) was used as coarse aggregate. POC in geopolymer concrete improves the compressive toughness compared to OPS geopolymer concrete because the porous POC aggregate increased the stiffness and improved the bond with mortar in concrete as the infilling effect of mortar into the pores strengthens the bond and enhances the crack growth resistance. Geopolymer concrete has lower capillary sorptivity, the usage of magnesium sulphate solution for sulphate resistance test showed negligible impact on geopolymer concrete due to the intrinsic nature of alumino silicate gels in geopolymeric materials. The results show that by utilizing POC and OPS structural grade lightweight geopolymer concrete can be produced. Graphical abstract: Highlights: Structural lightweight geopolymer concrete could be produced by using POC and OPS as coarse aggregate. The highest compressive strength was found for 100% POC (9–14 mm) as coarse aggregate in concrete. Compressive toughness and some durability properties of geopolymer concrete were investigated.